2006
DOI: 10.1111/j.1745-7254.2006.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine prevents apoptosis in spermatogenic cells after experimental testicular torsion/detorsion

Abstract: Aim: To determine whether sulfasalazine can prevent apoptosis in spermatogenic cells by preventing the activation of NF-κB in spermatogenic epithelium in experimental testicular torsion. Methods: Thirty-two adult male Sprague-Dawley rats were subjected to unilateral 720° testicular torsion for durations of 0 h and 2 h, then the torsion was relieved. The ischemic/reperfused testes were collected for the detection of NF-κB expression with Western blotting and immunohistochemistry techniques, and detection of apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…A number of studies have confirmed the pivotal role of NF‐κB in I/R injury cases . NF‐κB, which is a transcription factor that regulates the expression of multiple inflammatory and immune genes, plays a crucial role in host defense, chronic inflammatory diseases and even tumoural conditions .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have confirmed the pivotal role of NF‐κB in I/R injury cases . NF‐κB, which is a transcription factor that regulates the expression of multiple inflammatory and immune genes, plays a crucial role in host defense, chronic inflammatory diseases and even tumoural conditions .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we identified the SSZ‐triggered pro‐apoptotic pathway, which was dependent on caspase 8 activation. Conversely, SSZ has also been shown to induce survival in rat spermatogenic and human hepatoma cells 27,28 . The conflicting data regarding SSZ‐induced apoptosis are probably due to different drug concentrations and cell models used in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, SSZ has also been shown to induce survival in rat spermatogenic and human hepatoma cells. 27,28 The conflicting data regarding SSZ-induced apoptosis are probably due to different drug concentrations and cell models used in the different studies. Another possible explanation may be related to the direct 'paracrine' cell function modulation by inflammatory molecules (such as chemokines) that are secreted during incubation of the same cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although some investigators have also studied the right testis [2,4,13,[24][25][26]30,32], the left [1,3,[10][11][12][16][17][18][19][20][21][22]27,33,34,39,41] seems to be more commonly studied. Testicular torsion clinically occurs more often in the left testis [53].…”
Section: Discussionmentioning
confidence: 96%
“…The ability of several antioxidants including vitamins E and C, selenium, SOD, and catalase to prevent testicular injury in I/R model animals has been investigated [4]. The following compounds have also been tested in models of testicular I/R: melatonin [16,17], steroid [17], allopurinol [5], trapidil [1,18], propofol [19], zinc aspirate [20], taurine [21], vascular endothelial growth factor [22], epidermal growth factor [23], cyclosporine-A and FK 506 [2], α-lipoic acid [24], molsidomine [25], trimetazidine [3], raxofelast [12], vasoactive intestinal peptide [13], platelet-activating factor antagonist [14], nonsteroidal anti-inflammatory drugs [11,26], garlic extract [27], Lomodex-MgSO 4 [28], erdosteine [29], resveratrol [30], verapamil [31], ethyl pyruvate [32], caffeic acid phenethyl ester [33], and sulfasalazine [34]. However, none of them have found routine clinical application [2,10].…”
Section: Discussionmentioning
confidence: 99%